Changes in serum albumin levels and neutrophil–lymphocyte ratio in patients with convulsive status epilepticus. (4th May 2017) - Özdemir, Hasan H; Akil, Esref; Acar, Abdullah; Tamam, Yusuf; Varol, Sefer; Cevik, Mehmet Ugur; Arikanoglu, Adalet
Abstract : Aim: Inflammation may be involved in the ictogenesis and development of some partial epilepsies. Serum albumin levels and the neutrophil–lymphocyte ratio (NLR) are markers of inflammation. The aim of this study was to investigate the ability of serum albumin levels and NLR to predict inflammation in patients with convulsive status epilepticus (CSE). Methods: This retrospective study was conducted on 58 patients who were diagnosed with CSE and control group comprised of 58 healthy individuals. Albumin levels and NLR were evaluated during both the acute and subacute periods of CSE. Results: The average serum albumin levels were 3.27 ± 0.62 g/dL during the acute period and 3.4 ± 0.67 g/dL in the subacute period in the patient group and 3.92 ± 0.52 g/dL in the control group. Neutrophil counts were higher in patients in the acute phase of CSE, but lymphocyte counts were lower compared to the control group and the subacute phase. The average NLR values were 4.83 ± 5.1 in the acute period, 3.07 ± 3.02 during the subacute period and 1.98 ± 0.42 in the control group. Serum albumin and NLR levels were significantly different between the patients in the subacute and acute periods of CSE and the control group ( p < 0.05). There were significant negative correlational relationships between serum albumin and NLR levels ( p < 0.05). Conclusion: We found serum albumin levels were significantly lower and the NLR was significantly higher in the acute period of CSE. Neutrophil-mediated inflammation may be important in the aetiopathogenesis of CSE.